Foreign Borrowing and Economic Growth in Zambia: An Econometric Analysis - Mulumba, Clive Mutale (Graduate School of Business (GSB), 2018)
In the recent past, Zambia has increased its external borrowings significantly after reaching the Heavily Indebted Poor Countries (HIPC) completion point. The Zambian government has been on an ambitious borrowing spree with the intent that most of these funds would be channelled towards building and maintenance of key national infrastructure including roads and construction of new airports. This study undertook to answer the question, does increasing external debt affect growth of a nation’s economy? The thesis commenced an econometric study between the years 1980 to 2015 using publicly available data premised on the neoclassical economic growth model. The findings from this investigation show that shocks to external debt negatively impact the economic output of Zambia which is proxied by the Gross Domestic Product (GDP). Conversely, it was found that external debt stock could not reliably forecast future economic growth for the nation, a finding which in itself provides an area of further investigations. These research findings and recommendations make it clear that Zambia requires a comprehensive debt contraction and management framework to avoid the vagaries of short-term decisions which may not always be premised on sound economic thinking.